1993
DOI: 10.1364/josaa.10.001849
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity and disability glare in the middle years

Abstract: Spatial contrast sensitivity and disability glare were measured in a large sample (n = 90,30 per decade) of middle-aged subjects, aged 21-50 years, who had clear media and were ophthalmologically normal. We found no significant differences in the contrast sensitivities as a function of age in the middle years for (1) gratings generated on a monitor; (2) interference gratings generated in the retinal plane; (3) gratings in the presence of glare; and (4) mesopic increment thresholds with and without glare. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(15 reference statements)
3
4
0
1
Order By: Relevance
“…This finding is consistent with those described by Scharwey et al [25], who found that mesopic contrast acuity and glare sensitivity, measured using the Mesotest II, deteriorated in an age-dependent way in 117 healthy subjects. We are in agreement with Harrison et al [12] who found no significant differences in the sensitivity increment in the absence or presence of glare as a function of age across the middle years (21-50 years) in ophthalmologically normal subjects using sinewave gratings to measure the mesopic contrast sensitivity at four low spatial frequencies. We also observed homogenous results in the middle age groups (21-50 years) of our population.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with those described by Scharwey et al [25], who found that mesopic contrast acuity and glare sensitivity, measured using the Mesotest II, deteriorated in an age-dependent way in 117 healthy subjects. We are in agreement with Harrison et al [12] who found no significant differences in the sensitivity increment in the absence or presence of glare as a function of age across the middle years (21-50 years) in ophthalmologically normal subjects using sinewave gratings to measure the mesopic contrast sensitivity at four low spatial frequencies. We also observed homogenous results in the middle age groups (21-50 years) of our population.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, those aged fifty years or older had significantly larger k values (mean = 57.14) than younger participants (mean = 33.46), t(38) = 3.90, p < .01. In agreement with previous literature, this finding indicates that scatter within the eye increases over the age of fifty years [34][35][36].…”
Section: Combined Predictions Of Functional Contrast Thresholdssupporting
confidence: 93%
“…Given the well-established decline in visual function with age, both as a result of changes in the optics of the eye [34][35][36][43][44][45] and neural changes [46][47][48][49], it seems unlikely that the discrepancy in the older group's performance would be due to additional protective factors. A more likely explanation would be that the contrast threshold curve, upon which the estimations of retinal sensitivity are based, is not entirely representative for older observers.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting there is some disagreement as to how quickly color vision declines -for example, see Schieber (2006). 23 Higgins (1988), Harrison (1993), Jackson et al (1997), Jackson and Owsley (2000), and Schieber (2006). 24 Fozard and Salant (2001).…”
Section: Constructing the Indexmentioning
confidence: 99%